Evaluation of the mechanism of action of paracetamol, drotaverine, and peppermint oil and their effects in combination with hyoscine butylbromide on colonic motility: human ex-vivo study - Traserra, Sara; Barber, Claudia; Alcalá-González, Luis Gerardo; Landolfi, Stefania; Lange, Robert; Malagelada, Carolina; Corsetti, Maura; Jimenez, Marcel (Frontiers in Pharmacology, 2024)
Drotaverine, paracetamol, and peppermint oil are often prescribed for the treatment of gastrointestinal spasm and pain. This study aimed to evaluate the effect of these drugs alone and combined with the well-known antispasmodic hyoscine butylbromide on the human colon. Colon samples were obtained from macroscopically normal regions of 68 patients undergoing surgery and studied in muscle bath. Drotaverine, paracetamol, and peppermint oil were tested alone and in combination with hyoscine butylbromide on 1-spontaneous contractility induced by isometric stretch (in the presence of 1 µM tetrodotoxin) and 2-contractility induced by 10-5M carbachol and after 3-electrical field stimulationinduced selective stimulation of excitatory (in the presence of 1 mM Nω-nitro-L-arginine and 10 µM MRS2179) and 4-inhibitory (under non-adrenergic, non-cholinergic conditions) pathways. 5- Drotaverine alone was also tested on cAMP-dependent pathway activated by forskolin. Compared with the vehicle, drotaverine and paracetamol (10-9 -10-5M) did not modify spontaneous contractions, carbachol-induced contractions, and responses attributed to selective activation of excitatory pathways. The addition of hyoscine butylbromide (10-7-10-5M), concentration-dependently reduced myogenic contractions and carbachol-and electrical field stimulation-induced contractile responses. The association of paracetamol (10-4M) and hyoscine butylbromide (10-7-10-5 M) was not different from hyoscine butylbromide alone (10-7-10-5M). At higher concentrations (10-3M-3*10-3M), paracetamol decreased myogenic and carbachol-induced contractions. The adenylate cyclase activator, forskolin, concentration-dependently reduced contractility, leading to smooth muscle relaxation. The effect of forskolin 10-7M was concentration-dependently enhanced by drotaverine (10-6M-10-5M). Peppermint oil reduced myogenic activity and carbachol-and electrical field stimulation-induced contractions. The association of hyoscine butylbromide and peppermint oil was synergistic since the interaction index measured with the isobologram was lower than 1. No effect was seen on the neuralmediated inhibitory responses with any of the drugs studied although peppermint oil reduced the subsequent off-contraction. Drotaverine and hyoscine butylbromide have a complementary effect on human colon motility as one stimulates the cAMP inhibitory pathway and the other inhibits the excitatory pathway. Peppermint oil is synergic with hyoscine butylbromide suggesting that a combination therapy may be more effective in treating patients. In contrast, at therapeutic concentrations, paracetamol does not modify colonic contractility, suggesting that the association of paracetamol and hyoscine butylbromide has independent analgesic and antispasmodic properties.